THE ROLE OF HIGHER EDUCATION PROMOTION THROUGH ADVERTISING AND PUBLIC RELATIONS ON STUDENT DECISIONS TO CHOOSE A CAMPUS IN SAHID ISLAMIC RELIGION INSTITUTE, BOGOR - Pradia Nirwana , Testa; Permata Sari , Siska (JURNAL SAHID DA’WATII, 2022)
This study aims to determine the role of marketing promotion carried out by the Sahid Bogor Islamic Institute (INAIS) through advertising and public relations in attracting prospective new students, as well as knowing the student’s decision to choose the Sahid Bogor Islamic Institute. This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. The informants in this study were marketing staff and new INAIS students. The results of this study indicate that marketing promotions carried out by INAIS are through advertisements using conventional media and new media. Advertisements through conventional media are in the form of banners and brochures, while advertisements through new media use platforms such as YouTube, Instagram, and websites. Public relations activities carried out by INAIS include visits to potential high schools/vocational schools, as well as holding activities in collaboration with these schools. Several informants who were new students of INAIS admitted that they were interested in becoming students at INAIS because apart from being close to their domicile and affordable tuition fees, they were also interested in advertisements through new media that featured advantages such as available majors, active student activities, achievements, and scholarship offers.